The Effects of Two Instrumentation Techniques for VDW.Rotate Instruments on the Apical Extrusion of Debris and Irrigants: An In Vitro Study - Falakaloğlu, Seda; Yeniçeri Özata, Merve; İriboz, Emre (Journal of Dentistry Indonesia, 2022)
Objectives: This study compared the amount of apically extruded debris and irrigant using VDW.ROTATE instruments with different kinematics (continuous rotation and reciprocation motion) and the ProTaper Gold system. Methods: Sixty extracted mandibular premolar teeth were selected. The teeth were prepared for the agar gel model. The roots were randomly divided into three groups (n=20). In two groups, the root canals were instrumented using the following movement kinematics: VDW.ROTATE reciprocation motion and continuous rotation. In the other group, root canals were prepared with ProTaper Gold. Apically extruded debris and irrigant during instrumentation were collected into preweighed Eppendorf tubes and were assessed with an electronic balance. All procedures were performed in a 35oC hot water bath. The data were analyzed using the Shapiro–Wilk and Kruskal–Wallis tests at a 5% significance level. Results: ROTATE-Reciprocation extruded the least amount of debris, but this finding was not significant when compared with the amount of debris and irrigant extruded by the ProTaper Gold and ROTATE-Rotation (p>.05). Conclusion: All instrumentation kinematics were associated with apical debris and irrigant extrusion. Movement kinematics did not affect the amount of apically extruded debris and irrigants when using VDW.ROTATE instruments.